Determining the quasi monsoon front in the Indian Himalayas. (20th October 2021) - Mal, S.; Dimri, A.P.; Jeelani, G.; Allen, S.K.; Scott, C.A.; Arora, M.; Banerjee, A.; Lone, S.A.
Abstract: Precipitation over the southern rim of the Indian Himalayan Region (IHR) mainly occurs due to two dominant synoptic weather systems: Indian winter (IWM: December, January, February) and summer monsoon (ISM: June, July, August, September). The genesis and evolution of these systems are extensively researched. Additionally, geographical location, season, orography controls the strengths of these systems along and across the southern rim of the IHR. However, plausible positioning of the frontal threshold limit of precipitation during IWM and ISM over the IHR remains an elusive scientific question. Thus, with the help of water samples collected in the upper Bhilangana River Basin (BRB in the central Himalayas), an attempt has been made to assess this frontal threshold limit of precipitation and is defined as "quasi monsoon front (QMF)" in the IHR. Results show depleted (enriched) stable water isotopic values at higher (lower) altitudes suggesting an elevation control. The intercepts of local meteoric water lines (LMWLs) of glacier ice/glacier melt (2.5), snow packs/snow melt (7.7), and stream water (10.3) reflect mixing of precipitation due to IWM and ISM. The d-excess values in water samples lie between the d-excess value of a typical IWM (~20‰) and ISM (~10‰), suggesting mixing of moisture from both Atlantic ocean – Mediterranean sea and Indian ocean-Bay of Bengal-Arabian sea. The tracer based hydrographic analysis indicates dominance of snow melt contributions to the regional hydrology. Hybrid Single Particle Lagrangian Integrated Trajectory Model (HYSPLIT) model in the back trajectory mode estimates moisture sources of the IWM and ISM. Based on precipitation isotopic composition and associated moisture source regions, QMF oscillates in the northwest and southeast direction of the IHR depending on the strength and/or weakness of IWM and ISM. This work hypothesizes for upscale determination and description of the pulsatory extension of QMF in the central Himalayas (along BRB).